1989
DOI: 10.1104/pp.91.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of a Specific Cell Wall Layer in Regulation of Deep Supercooling of Xylem Parenchyma

Abstract: Current theory indicates that the structure of the cell wall is integral to the ability of a tissue to exhibit deep supercooling. Our previous work has indicated that the structure of the pit membrane and/or amorphous layer (protective layer), rather than the entire cell wall, may play a major role in deep supercooling (21,22). The present study indicates a shift in the low-temperatureexotherm of current year shoots of peach can be induced by soaking twigs in water over 3 to 10 days. Altematively, these shifts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…Slight extraction along the surface of the primary cell wall layer was observed in some cells with a small proportion of cells showing a slight loosening of the amorphous layer (Fig. 8) Regarding these questions, the present study and our previous work (19,21,22) indicate the structure of the pit membrane and underlying amorphous layer of xylem parenchyma may play an integral role in regulating deep supercooling of xylem tissues. Although the secondary cell wall provides the tensile strength required to withstand the negative pressures that occur during deep supercooling (10), it is our premise that the structural characteristics ofthe pit membrane act as a limiting factor in defining the ability of a cell to retain water in a metastable equilibrium against the large vapor pressure gradient generated during deep supercooling (11).…”
supporting
confidence: 45%
See 1 more Smart Citation
“…Slight extraction along the surface of the primary cell wall layer was observed in some cells with a small proportion of cells showing a slight loosening of the amorphous layer (Fig. 8) Regarding these questions, the present study and our previous work (19,21,22) indicate the structure of the pit membrane and underlying amorphous layer of xylem parenchyma may play an integral role in regulating deep supercooling of xylem tissues. Although the secondary cell wall provides the tensile strength required to withstand the negative pressures that occur during deep supercooling (10), it is our premise that the structural characteristics ofthe pit membrane act as a limiting factor in defining the ability of a cell to retain water in a metastable equilibrium against the large vapor pressure gradient generated during deep supercooling (11).…”
supporting
confidence: 45%
“…George (10) and Wisniewski et al (19,20) suggested that the structure of the pit membrane and underlying amorphous layer of xylem parenchyma may regulate deep supercooling of xylem tissues. Later work provided evidence that soaking stem segments in water for 3 to 10 d resulted in a partial degradation of the pit membrane, and a marked shift of the LTE' to warmer temperatures (21). These effects were inhibited by cycloheximide, indicating possible enzymatic cell wall autolysis.…”
mentioning
confidence: 99%
“…5), palm leaves with siliceous cell walls (Larcher et al, 1991), and xylem ray parenchyma cells in tropical and subtropical stems (Kuroda et al, 1997) can persist in supercooling down to -10 and -12 °C. In tissues with densely lignified or cutinized barriers, the propagation of ice is delayed or inhibited, and the cell wall rigidity can lead to increased cell tension and reduced cell dehydration (Wisniewski and Davis, 1989;Rajashekar and Burke, 1996). Deep supercooling in some flower primordia of winter buds is possible down to -20 to -25 °C (e.g., Kaku et al, 1980;Ishikawa and Sakai, 1981), in shoot primordia down to -20 to -30 °C, and in wood parenchyma and xylem rays of many forest and fruit trees and shrubs of the temperate zone down to -30 to -50 °C (e.g., Quamme et al, 1972;George et al, 1974;Gusta et al, 1983).…”
Section: Injury Patterns Of Cold and Frost And Acquisition Of Resistamentioning
confidence: 99%
“…In X. hymenachne (Fig. 4), the walls of the stomata guard cells were covered internally by a special layer, called protective layer (O'Brien, 1970) or secondary cellulosic layer (Czaninskiy, 1973), which was reported for the parenchymatous cells of the secondary xylem by Barnett et al (1993), Chaffe (1974), Foster (1967 and Wisniewski & Davis (1989). Such a protective layer formed electron dense ramified clusters (Fig.…”
Section: Resultsmentioning
confidence: 83%